Periprocedural Coagulation Status in Percutaneous Interventions - Soumil Singhal; Mangerira Chinnappa Uthappa (Journal of Clinical Interventional Radiology ISVIR)
Hemostasis is a very elaborate process, and its knowledge is essential for every interventional radiologist. Abnormal coagulation parameters are associated with an increased risk of bleeding and require appropriate management. This review aims to briefly discuss the pathophysiology of hemostasis, the role of currently available pharmacological agents affecting hemostasis, and the management of hemostasis during various percutaneous interventional procedures. A preprocedure proforma, when used as a checklist, can reduce procedure-related complications.